PUBLIC AWARENESS AND ACCEPTANCE TOWARDS TRANSPORTATION LOW CARBON CITY PROGRAMME. A COMPARISON STUDY OF MBSA AND DBKL - Nasrudin, Na’asah; George, Ainatul Isnoriza; Abdullah, Yusfida Ayu; Marzukhi, Marlyana Azyyati; Oliver Hoon Leh, Ling; Rashid, Kushairi (PLANNING MALAYSIA, 2020)
This paper examines public awareness and acceptance towards Transportation Low Carbon City’s (LCC) programme by two local authorities: Kuala Lumpur City Hall (DBKL) and Shah Alam City Council (MBSA). This paper also will measure the residents’ satisfaction level on the LCC programme initiatives prepared by both authorities. The data were gathered through a survey conducted randomly from 202 respondents who represented the residents of Kuala Lumpur city and 122 respondents who represented the residents of Shah Alam city. The findings suggested that the awareness of the respondents about the Transportation LCC’s programme was more positive in Kuala Lumpur as compared to Shah Alam. This was because almost 90 per cent of Kuala Lumpur respondents were aware of the programme. For feedback of willingness to change to non-motorised transportation as a support to Transportation LCC programme, Kuala Lumpur had a bright hope to fully achieve the successfulness of the LCC’s programme as compared to Shah Alam. With regards to implementation of public transportation, the majority of the both respondents’ groups agreed that the available public transportation was reliable, well-connected and reachable for their desired destination. This comparison study is essential to know how well the local authority manages their LCC programme. It is hoped that the two local authorities can learn and cooperate in future to make this programme a success.